Mujeres y mercado de trabajo informal en la ciudad de Bogotá. Una aproximación experimental (2020)
Whilst some theorists as represented by De Soto argue informality is due to a preference- based rational decision to avoid paying taxes, others consider it is more related to an "escape" from poverty as a unique option. The majority of informal workers in Bogota are women, most of whom do not have social security coverage or job stability. This research investigates to what extent female workers in the city of Bogota, Colombia prefer to work in the informal labor market. The aim of this work was to test De Soto's hypothesis and analyze women's participation in the informal labor market of the city of Bogota from an experimental approach. The study was based on an experiment targeting 500 women participants, formal and informal workers, from the city of Bogota. We designed a set of games as means to evaluate social norms, evasion of taxes, risk and temporary discount. The information obtained from these games was then analysed by descriptive statistics including regressions and test of means. The results indicated there are not significant differences in behavior between formal and informal female workers. Both groups tend to avoid taxes payment with similar levels of risk and social norms. Therefore, the informal workers are people that formal market could not employ.